Data Resource Profile: The China National Health Survey (CNHS). (13th August 2014) - He, Huijing; Pan, Li; Pa, Lize; Cui, Ze; Ren, Xiaolan; Wang, Dingming; Liu, Feng; Wang, Xianghua; Du, Jianwei; Wang, Hailing; Wan, Shaoping; Zhao, Jingbo; et al.
Abstract: The China National Health Survey (CNHS) is the first nationwide multi-ethnic cross-sectional interview and health examination conducted from 2012 to 2017. The survey is designed to study reference intervals for physiological constants as well as determinants of noncommunicable diseases among different ethnic populations in different areas, so that the data can be used to enhance clinical diagnosis strategies and health promotion. CNHS used a stratified, multistage cluster sampling method to obtain a sample of 53 895 people aged 20-80 years in 10 ethnic groups from 11 provinces or autonomous regions all over China. Blood samples were collected from each participant for the establishment of the China Multi-Ethnic Biobank (CMEB). CNHS collected data on demographic and socioeconomic information, lifestyle factors, anthropometric measures, laboratory tests and clinical profiles. These data provide a comprehensive resource for further study on risk factors of noncommunicable disease among different ethnic groups. Information about the CNHS database, including publication list, introduction of the survey design and methods, and guidelines for submitting electronic forms of data application, is available at [http://www.bmicc.cn/web/share/home ].